(untitled) (Revista Apotheke, 2024)
This article proposes the use of drama as an educational resource, considering its potential to arouse enthusiasm, transmit ideas, principles and values, in order to stimulate students’ belief in their personal power. The text characterizes the notion of drama based on the philosophical and educational conceptions of John Dewey, emphasizing the concepts of aesthetic experience and imagination derived from the works Democracy and education, How we think and Art as experience. With the purpose of encouraging teachers to use drama, the article presents a thought experiment based on Dewey’s notion of reflective thinking. It involves simulating a class in which the teacher proposes a problematic situation to the students: how to take a trip using unusual means of transportation. The conclusion refers to the concepts addressed in the article and the use of the thought experiment as contributions to the development of aesthetic sensitivity.